2020
DOI: 10.1088/1741-4326/ab9669
|View full text |Cite
|
Sign up to set email alerts
|

Core tungsten transport in WEST long pulse L-mode plasmas

Abstract: Tungsten transport is investigated in WEST long pulse L-mode plasmas operated with the strike point on the actively cooled upper tungsten divertor. The pulses are mostly heated by lower hybrid waves. It is experimentally found that tungsten does not centrally accumulate throughout these ∼ 30 s reproducible discharges despite large normalised electron density gradients R/Ln e. To explain these observations, turbulent and neoclassical transport of electrons and tungsten ions are computed with GKW [1] and NEO [2,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
41
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(44 citation statements)
references
References 58 publications
3
41
0
Order By: Relevance
“…Such ion density ratios of n 27 /n 26 are plotted in figure 10. The results are fairly in good agreement with the ratios of the ionization equilibrium model, which were calculated adopting ionization and recombination rate coefficients of atomic data and analysis structure (ADAS) database 4 and local T e and n e measured by Thomson scattering, except for radial regions where the ion densities are vanishingly small. The agreement seems to be better for the ratios obtained taking the proton collision effects into account.…”
Section: Assessment Of Tungsten Densitysupporting
confidence: 77%
See 1 more Smart Citation
“…Such ion density ratios of n 27 /n 26 are plotted in figure 10. The results are fairly in good agreement with the ratios of the ionization equilibrium model, which were calculated adopting ionization and recombination rate coefficients of atomic data and analysis structure (ADAS) database 4 and local T e and n e measured by Thomson scattering, except for radial regions where the ion densities are vanishingly small. The agreement seems to be better for the ratios obtained taking the proton collision effects into account.…”
Section: Assessment Of Tungsten Densitysupporting
confidence: 77%
“…The surpression of tungsten accumulation was observed also in Alcator C-Mod H-mode plasmas [3] with ICRH heating only. In long pulse WEST L-mode plasmas, it was reported that turblent transport manifesting at high ratios of electron temperatures to ion temperatures (𝑇𝑇 e 𝑇𝑇 i ⁄ ) mitigated tungsten accumulation [4]. Although such driving mechanisms have been identified with tokamak machines, tungsten transport is still hard to predict mainly due to the fact that subtle change in plasma profiles result in significant effects on the tungsten transport.…”
Section: Introductionmentioning
confidence: 99%
“…These improvements occurred with no changes to the LHCD power or plasma current and were concurrent with increases in the electron density and radiated power, suggesting improved confinement. A likely explanation is the suppression of ITGdriven turbulence due to main ion dilution, as observed in N2 seeding experiments in WEST [36], and/or modification of the density profile, as observed in powder injection experiments on AUG [15], W7-X [20], and LHD [22].…”
Section: Discussionmentioning
confidence: 97%
“…On the other hand, gaseous N 2 seeding experiments on WEST [36] have observed increases in confinement without density profile modification. In these experiments, fuel dilution was the dominant mechanism for turbulence suppression.…”
Section: Experimental Observations Of Improved Confinementmentioning
confidence: 99%
“…It is therefore essential to understand the mechanisms for the release and transport of W into the core, either from the divertor plates or from the walls of the machine onto which W has been deposited during previous plasma operations (e.g. Dux et al 2011, Yang et al 2020. JET, with its ITER-like wall (ILW) of Be in the main chamber and W in the divertor, is ideally suited to such studies (Casson et al 2020).…”
Section: Introductionmentioning
confidence: 99%